Between form and faith : Graham Greene and the Catholic novel - Sampson, Martyn (Studies in the Catholic imagination., 2021)
"What is a "Catholic" novel? This book analyzes the fiction of Graham Greene in a radically new manner, considering in depth its form and content, which rest on the oppositions between secularism and religion. Sampson challenges these distinctions, arguing that Greene has a dramatic contribution to add to their methodological premises. Chapters on Greene's four "Catholic" novels and two of his "post-Catholic" novels are complemented by fresh insight into the critical importance of his nonfiction. The study paints an image of an inviting yet beguilingly complex literary figure"--